34 FAMILIAL LATE-ONSET SPEECH SLURRING AND IMBALANCE. (1st January 2005) - Paravar, T.; Baloh, R. W.; Jen, J.; Perlman, S.
Abstract : Objective: To describe the clinical profile and understand the genetic basis of a family with late-onset idiopathic gait disorder affecting multiple family members. Background: Ataxia is a clinically and genetically heterogeneous condition. Acquired causes include congenital malformations, trauma, metabolic/toxic, infectious, para-infectious, or neoplastic. In the inherited syndromes, mode of inheritance may be autosomal dominant or recessive. Spontaneous mutations have also been identified in sporadic cases. Although gene tests are available for several syndromes, the responsible genes for many ataxia syndromes remain unknown. Methods: Evaluation consisted of relevant questionnaires and history, a neurologic exam, and genetic testing. Results: The family consisted of at least 3 generations of affected individuals with key clinical features including gait instability, eye movement abnormalities, dysarthria, and terminal dysmetria. Conclusion: Mode of inheritance is most consistent with autosomal dominant inheritance. All features are consistent with Spinocerebellar Ataxia (SCA) of pure cerebellar origin Genetic testing with the standard Ataxia Panel excludes etiologies that have available genetic tests. We will continue to search for the genetic cause despite negative findings to date.